Pharmacogenetics of medication-related osteonecrosis of the jaw: a systematic review and meta-analysis. Issue 3 (March 2020) - Guo, Z.; Cui, W.; Que, L.; Li, C.; Tang, X.; Liu, J.
Abstract: Medication-related osteonecrosis of the jaw (MRONJ) is a severe complication that can develop in patients treated with anti-resorptive drugs. Although the pathogenesis of MRONJ is still unclear, genetic factors have a demonstrated important role. Thus, the aim of this study was to perform a systematic review on the pharmacogenetics of MRONJ. Studies published until March 2019 were retrieved from eight databases and were selected by two independent reviewers. Evidence on several genetic polymorphisms was summarized and a meta-analysis was conducted when possible. Fourteen studies involving 1515 participants were eligible for systematic review. For CYP2C8 rs1934951, no significant difference was observed between the MRONJ and non-MRONJ groups (odds ratio (OR) 2.04, 95% confidence interval (CI) 0.88–4.73, P = 0.09). However, a subgroup analysis based on only multiple myeloma status showed a positive association (OR 3.64, 95% CI 1.29–10.30, P = 0.01). PPARG rs1152003 was not differently distributed between groups (OR 0.25, 95% CI 0.01–9.92, P = 0.46). Also, VEGF rs3025039 was found to be correlated with the occurrence of MRONJ (OR 0.35, 95% CI 0.15–0.82, P = 0.02). CYP2C8 rs1934951 (in multiple myeloma patients) and VEGF rs3025039 are associated with the development of MRONJ in patients treated with bisphosphonates. The results are promising and call for new trials with a larger sample to further explore this growing field.